Urbanization-induced soil organic carbon loss and microbial-enzymatic drivers: insights from aggregate size classes in Nanchang city, China - Zhang, Foyi; Zhong, Jialin; Zhao, Yuquan; Cai, Changyongming; Liu, Wei; Wang, Qiong; Wang, Wenjie; Wang, Huimei; Jiang, Xueru; Yuan, Renqiang (Frontiers in Microbiology, 2024)
Soil microorganisms and enzymes play crucial roles in soil organic carbon (SOC) sequestration by promoting soil aggregate formation and stability and by participating in SOC cycling and accumulation. However, the effects by which soil microorganisms and enzymes act as mediators driving dynamic changes in SOC during rapid urbanization remain unclear. Therefore, this study selected the built-up area of Nanchang City, China (505 km 2 ), as the study area. Sampling surveys were conducted using 184 sample plots stratified based on the proportion of impermeable surface area to distinguish different urbanization levels. The driving factors of dynamic changes in SOC of different aggregates during the process of urbanization were analyzed using the soil microbial community and enzyme activities. The results demonstrated that with an increase in urbanization intensity, both SOC content and stock exhibited a significant decline. Particularly, the SOC content of >0.053 mm aggregates decreased significantly by 26-39% (p < 0.05). The highest SOC stock and contribution rate were observed in the 0.25-1 mm aggregates, and they were significantly influenced by urbanization (p < 0.05). In addition, the biomass of gram-positive bacteria (G+) and actinomycetota, and the activities of N-acetylglucosaminidase and acid phosphatase (AP) were significantly higher in low-urbanization areas than in high-urbanization areas (p < 0.05). Redundancy analysis indicated that SOC of each aggregate was positively correlated with fungi, arbuscular mycorrhizal fungi, G+, gram-negative bacteria, actinomycetota, protozoa, β-1,4-glucosidase, N-acetylglucosaminidase, AP, urease, and catalase. Compared to soil enzymes, soil microorganisms exhibited a greater role in SOC sequestration (22.7%). Additionally, a structural equation model indicated that urbanization can directly or indirectly lead to a decrease in SOC of aggregates by altering soil physicochemical properties and affecting microbial and enzyme dynamics. However, the larger tree height, crown width, Shannon diversity index, and Simpson evenness index mitigate the negative impacts of urbanization on SOC. In the future, it is important to promote SOC sequestration that focus on improving soil nutrients, maintaining soil structure, protecting existing urban trees, and enhancing plant diversity during the urbanization process.